Using different carrots: How incentivization affects proficiency testing outcomes. (11th June 2019) - Gass, Susan; Van Gorp, Koen; Winke, Paula
Abstract: This study represents program‐level action research. A U.S. university Spanish language program had a goal for students to reach the ACTFL (2012) Intermediate Mid level after 2 years. An empirical question that resulted after regular end‐of‐year testing was whether the students were doing their best on assessments. To investigate this, 253 end‐of‐second‐year students were divided into two experimental conditions: (a) 95 students received up to 10% of their final grade based on meeting the speaking goal, and (b) 73 students received up to 5% of their grade on the same criterion. Eighty‐five students formed a control group with no grading incentive. All took ACTFL tests in speaking (the Oral Proficiency Interview‐computerized [OPIc]), listening (Listening Proficiency Test), and reading (Reading Proficiency Test). The group whose OPIc score counted for 10% performed significantly higher than other two groups. Females were more positively affected by the incentivization. Programs with language goals should consider incentivized proficiency‐based exit tests to motivate their students (Chalhoub‐Deville, 1997). The Challenge: Routine proficiency testing offers an important way to monitor a program's learning targets and measure students' language development. However, it is not clear how seriously students take end‐of‐course assessments. To what extent does adjusting the incentives influence students' scores? How can students be encouraged to do their best? Video_Abstract_and_Discussion